In vitro effects of alcohol-containing mouthwashes on human enamel and restorative materials - José Eduardo Pelizon PELINO; Alan PASSERO; Airton Abrahao MARTIN; Christine Ann CHARLES (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The objective of this study was to evaluate the in vitro effects, including surface morphological characteristics and chemical elemental properties, of different mouthwash formulations on enamel and dental restorative materials, simulating up to 6 months of daily use. Human enamel samples, hydroxyapatite, composite resin, and ceramic surfaces were exposed to 3 different mouthwashes according to label directions - Listerine® Cool Mint®, Listerine® Total Care, and Listerine® Whitening - versus control (hydroalcohol solution) to simulate daily use for up to 6 months. The samples were analyzed using scanning electron microscopy (SEM), infrared spectrophotometry (µ-Fourier transform infrared microscopy), energy-dispersive X-ray (EDX) spectroscopy, and color analysis before and after exposure. No relevant changes were observed in the morphological characteristics of the surfaces using SEM techniques. The physical and chemical aspects of the enamel surfaces were evaluated using mid-infrared spectroscopy, and EDX fluorescence was used to evaluate the elemental aspects of each surface. There was no variation in the relative concentrations of calcium and phosphorus in enamel, silicon and barium in composite resin, and silicon and aluminum in the ceramic material before and after treatment. No relevant changes were detected in the biochemical and color properties of any specimen, except with Listerine® Whitening mouthwash, which demonstrated a whitening effect on enamel surfaces. Long-term exposure to low pH, alcohol-containing, and peroxide-containing mouthwash formulations caused no ultra-structural or chemical elemental changes in human enamel or dental restorative materials in vitro.